The Link between Urbanization and Climatic Factors : A Concept on Formation of Urban Heat Island - Nurakmal, Abdullah@ Goh Tuo Ho; Khairul Nizam, Abdul Maulud; Mazlan, Mohd Tahir; Muhammad, Nor; Che-Ani, A. I. (WSEAS, 2010)
Increasing the number of population, pollutions, urban expansion and many other kinds of urbanization factors in metropolitan areas are affected climatic factors and vice versa. In fact, there is a correlation between these two factors in general. This paper put forward the conceptual model and two hypotheses. In order to test the model, UHI mapping has been carried out in Tehran as a case study. The investigation has been done at macro-level to get surface temperature. The methodology employed is to use satellite image with a thermal band (obtained on 18 July 2000). To map out the UHI, mapping of LST and NDVI were necessary and then overlaid them and extracted maximum temperature value for both urban and rural areas. The results show that the maximum urban and rural temperature values are 39°C and 27°C respectively. Therefore, daytime Tehran surface UHI shows 12ºC of difference between urban and rural areas which is quite strong. Analyzing the data specified that the urbanization factors have direct impact on increasing the UHI intensity in Tehran metropolitan area.